State-of-the-art electrochromic thin films devices, fabrication techniques and applications: a review - Muhammad Yaseen; Muhammad Arif Khan Khattak; Abbas Khan; Shaista Bibi; Mohamed Bououdina; Muhammad Usman; Niaz Ali Khan; Azhar Ali Ayaz Pirzado; Rasha A. Abumousa; Muhammad Humayun (Nanocomposites)
Electrochromic (EC) thin films have received considerable attention due to their potential applications in various fields such as smart windows, electrochromic displays, and energy storage devices. This review highlights various methods used for the fabrication and functionalization of EC films for various applications. Various techniques for EC thin film deposition ranging from solution-processable, low-temperature approaches such as sol-gel, spin coating, dip coating, and spray pyrolysis, to advanced techniques for deposition such as physical vapor deposition, chemical vapor deposition, and sputtering are summarized in this review. In addition, various applications of EC thin films and the outcome of different deposition approaches on the opto-electrochromic properties of EC thin films have been discussed elaborately. This review has the potential to spark the interest of researchers from a broad range of disciplines, including photocatalysis, electrocatalysis, nanotechnology and materials science.